Respuesta :

Answer:

Then the midpoint is (2, -2)

Step-by-step explanation:

We treat the x- and y-coordinates separately, first finding the average (mean) of the x-coordinates and then the average of the y-coordinates:

xm = (-1 + 5)/2 = 2

ym = (1 - 5)/2 = -2

Then the midpoint is (2, -2)

Answer:

(2,-2)

Step-by-step explanation:

Two points are given to us and we need to find the midpoint of those two points. The points are

(-1,1) and (5,-5) . Let us say we have two points ( x1,y1) and ( x2 , y2) . The midpoint will be ,

[tex]\implies Midpoint =\bigg( \dfrac{x_1+x_2}{2},\dfrac{y_1+y_2}{2} \bigg) \\\\\implies Midpoint = \bigg( \dfrac{-1+5}{2},\dfrac{1-5}{2}\bigg)\\\\\implies Midpoint = \bigg( \dfrac{4}{2},\dfrac{-4}{2}\bigg)\\\\\implies \red{Midpoint = ( 2 , -2) }[/tex]